Detection of Viable Zygosaccharomyces rouxii in Honey and Honey Products via PMAXX-qPCR - Shiqiong Chen; Qingyan Tang; Jianqiang Geng; Yanqin Liu; Jie Jiang; Xuefeng Cai; Hong Cao; Yantao Wu; Yan Ren; Kai Liu; Yue Cao (Journal of Food Quality)
In order to establish a fast detection method for the living Zygosaccharomyces rouxii (Z. rouxii) cells in honey and honey products, the performance of propidium monoazide bromide (PMA) and enhanced propidium monoazide bromide (PMAXX) combined with real-time PCR for detecting living cells of Z. rouxii was compared. PMAXX was chosen as the added agent because of its better performance. The optimal concentration of PMAXX was found to be 76.92 μM in cell solution (the cell concentration was 1.0 × 108 CFU/mL). The LODs of PMAXX-qPCR in detecting Z. rouxii in pure MEA and honey solution were found to be 103 and 101 CFU/mL, respectively. Living Z. rouxii cells in 18 real honey samples were detected using this PMAXX-qPCR method and compared with the plate count method. The two methods showed consistent detection results in ten negative samples. In the other eight plate count zero but PMAXX-qPCR-positive samples, further verification experiments showed that six of the PMAXX-qPCR-positive samples contained viable but nonculturable (VBNC) Z. rouxii, while the other two PMAXX-qPCR-positive samples may have contained DNA contamination of Z. rouxii. This method is not only fast and sensitive but also can detect both culturable and viable but nonculturable Z. rouxii. This study provides a promising fast and culture-independent method for the detection of living Z. rouxii cells in honey and honey products.